EPOXY POLYMERS BASED ON DIGLYCIDYL ETHERS WITH CYCLIC GROUPS - Givi Papava; Nora Dokhturishvili; Marina Gurgenishvili; Ia Chitrekashvili; Zurab Chubinishvili (World Science, 2020)
Glycidyl ethers of polycyclic bisphenols of norbornan type and their phenyl substituted derivatives were obtained and studied. They were solidified by diaminodiphenylsulphon and methyltetrahydrophthalic anhydride. The data of the termogravimetric analysis of the obtained polymers showed that they are characterizes by high thermal – and heat stability. The properties of polymers depend on the structure of the hardener and its chemical nature as well. The properties of polymers were sharply changed when glycidyl derivatives of bisphenols were cured by hardeners of different chemical structure. The presence of cyclic structures in the hardener molecule causes considerable increase of their thermal stability. Polymers on the basis of chlorine substituted glycidyl ethers of polycyclic bisphenols are characterized by incombustibility.